FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN PENERAPAN E-LEARNING SEBAGAI MEDIA PENDUKUNG PEMBELAJARAN di FAKULTAS EKONOMI UNTAN - Pebrianty, Wenny (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2010)
Changes in content-based curriculum to competence-based curriculum require an urgent implementation of e-learning as learning supporting media owing to learning process undergoes radical changes from lecturer’s-oriented into student’s oriented. The present study aims to examine some factors affecting the acceptance of e-learning application in higher education. By making use of regression analysis, the results show that intrinsic motivation factors such as ease of e-learning usage and desireness to use e-learning influence significantly on willingness to use e-learning.   Keywords: higher education curriculum, e-learning application, learning supporting media.